RESEARCH TRENDS AND SOLUTIONS FOR SECURE TRAFFIC MANAGEMENT OF SDN - Pandey, Ravi Shankar; Srivastava, Vivek; Yadav, Lal Babu (APTIKOM Journal on Computer Science and Information Technologies, 2017)
Software Defined Network (SDN) decouples the responsibilities of route management and datatransmission of network devices present in network infrastructure. It integrates the control responsibility at thecentralized software component which is known as controller. This centralized aggregation of responsibilities mayresult the single point of failure in the case malicious attack at the controller side. These attacks may also affect thetraffic flow and network devices. The security issues due to such malicious attacks in SDN are dominating challengesin the implementation and utilization of opportunities provided by this new paradigm. In this paper we haveinvestigated the several research papers related to proposal of new research trends for security and suggestionswhich fulfil the security requirements like confidentiality, integrity, availability, authenticity, authorization,nonrepudiation, consistency, fast responsiveness and adaptation. We have also investigated the new future researchfor creating the attack free environment for implementing the SDN.